Identity Does Matter: A Comparative Study of Turkey–Bulgaria's Accession into the European Union - Maulana, Zain; Pangestika, Meitha Azzahra (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2024)
The European Union’s enlargement process, guided by the Copenhagen Criteria, is a multi-faceted exercise influenced by both technical and socio-cultural factors. While the Criteria set standards in political, economic, and legal spheres, the accession of nations often hinges on deep-rooted perceptions of identity and cultural congruence. using the contrasting cases of Bulgaria and Turkey, this article explores the nuances of EU accession. Bulgaria’s relatively smooth accession, despite its initial economic and political challenges, stands in stark contrast to Turkey’s prolonged and complex negotiation process. Although Turkey has made significant reforms aligning with EU standards and showcased impressive economic growth, underlying factors such as historical tensions, cultural differences, geographical concerns, and human rights issues have impeded its membership. This comparative analysis underscores the interplay of objective criteria and subjective notions of European identity in the EU enlargement process.